THE RELATIONSHIP BETWEEN THE PRACTICE OF OBLIGATORY PRAYERS AND STUDENT’S DISCIPLINE CHARACTER: FOCUSING ON TIME DISCIPLINE AND ENGAGEMENT - Risqiya Qurrota A'yun; Syaripudin; Waluyo Erry Wahyudi (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study is motivated by the phenomenon of declining consistency in the performance of the five daily prayers (ṣalāt) and the low level of disciplinary character observed among some tenth-grade students at MAN 2 Bandar Lampung, despite the fact that prayer theoretically serves an educational function in fostering self-control, orderliness, and obedience to rules. This condition raises a critical question regarding the extent to which the performance of the five daily prayers is associated with students’ disciplinary character within the context of Islamic religious education in madrasahs. The objective of this study is to examine the relationship between the consistency of performing the five daily prayers and the disciplinary character of tenth-grade students. The study employed a quantitative approach with an ex post facto research design, involving 77 students selected through a simple random sampling technique. The research instrument consisted of a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis included prerequisite tests (normality, homogeneity, and linearity), followed by the Mann–Whitney test, as well as regression analysis using the F-test, t-test, and coefficient of determination. The results indicate that the performance of the five daily prayers is significantly associated with students’ disciplinary character, with a significance value of 0.000 and an R Square value of 0.478, indicating that 47.8% of the variation in disciplinary character is explained by the consistency of prayer performance. These findings suggest that the five daily prayers are not merely acts of worship, but also function as a mechanism for cultivating time discipline and self-control. The study concludes that habituation to the performance of the five daily prayers can serve as an effective strategy for strengthening students’ character education, particularly in the aspect of discipline, within the madrasah environment.